Determination of pulp production paramemeters from common hazelnut (Corylus avellana L.) wood using soda method - Ayhan Gençer; Ufuk Özgül (Turkish Journal of Forestry, 2015)
In this study, pulp and papers were produced from common hazelnut (Coryllus avellana L.) wood by using Soda (NaOH) methods. According to the literature, chip/solution ratio was chosen as 1/5, cooking temperature was 170±2 °C and duration of reaching maximum temperature was 90 minutes. NaOH ratios were chosen as %20, %22, % 24 and %26, cooking durations at maximum temperature were 60 and 90 minutes and 8 cooking were carried out. According to the results, as cooking duration increased kappa number and viscosity was reduced, screened yield was increased with %20 and %22 NaOH and decreased at %24 and %26 NaOH. Investigating the effect of cooking duration, screened yield increased at %24 NaOH with 150 minutes, it was decreased at 180 minutes with same concentration. Thus, yield lost was observed at increased cooking duration with high concentrations. Same situation was observed and it was proved that %24 NaOH and 150 minutes cooking duration having 883.13 cm3/g viscosity value and for 180 minutes it was 857.05 cm3/g.